Site‐Specific Soil Properties of the US Climate Reference Network Soil Moisture. Issue 11 (21st November 2016) - Wilson, Timothy B.; Baker, C. Bruce; Meyers, Tilden P.; Kochendorfer, John; Hall, Mark; Bell, Jesse E.; Diamond, Howard J.; Palecki, Michael A.
Abstract : Core Ideas: This study quantifies the variability of soils at US Climate Reference Network sites. Soil properties were determined from the analysis of soil core samples. Soil properties displayed large variability with depth and location within and among sites. Variability of soil properties helped determine and interpret soil moisture variability. The objective of this study was to provide direct measurements of soil properties for 70 of the 114 US Climate Reference Network (USCRN) sites across the continental United States. Soil properties determined from the analysis of soil core samples include the particle size distribution (PSD, consisting of sand, silt, and clay contents), soil texture classifications, bulk density (BD), and the soil moisture content at water potentials of 33 kPa (field capacity, FC) and 1500 kPa (wilting point, WP). Sand, silt, and clay contents of the 70 sites indicated about 10 soil texture classifications as follows: three sites with loamy sand, 15 with sandy loam, two with clay, 11 with silt loam, five with clay loam, 10 with loam, seven with sand, eight with silty clay loam, four with sandy clay, and three with silty clay. The comparison of soil properties among soil depths and pits indicated considerable variability, with the silt, clay, and sand contents varying more with soil depth than with location at individual sites. The silt content tended to decrease with soil depth, clay tended to increase, and sand tended to vary randomly with depth. Regression lines fitted to values of FC and WP between the pits indicated a slope > 0.8, R 2 > 0.88, and RMSE ranging from 2.7 to 4%. Compared with FC and WP, BD was less consistent among the pits, with slope = 0.6, R 2 = 0.4, and RMSE of about 0.2 g cm −3 .